APLIKASI E-SURAT SEBAGAI UPAYA PENDUKUNG TATA KELOLA PEMERINTAHAN DI DESA KUKUH, KERAMBITAN, TABANAN, BALI - I Putu Susila Handika; I Kadek Susila Satwika (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2021)
The electronic based government system causes a change in the conventional mindset towards digitalization.. This was also done by Kukuh Kerambitan Village, Tabanan Regency, Bali Province. To Support the electronic based government system, research was carried out on the development of the E-Letter information system in Kukuh Kerambitan Village. This study aims to assist village officials in the letter disposition process to be faster and the process of making activity reports easier. This research was developed using the prototyping method so that users can evaluate the application at the design stage. The E-Letter application was built on a web basis using PHP programming language and laravel framework. From the results of the blackbox test, it shows that the E-Surat application has been running according to the functional needs and the results of the usability test also show that most of the average value of each question is greater than the middle value on the likert scale 1-7, which means the application can be accepted by the user.